Molecular urothelial tumor cell subtypes remain stable during metastatic evolution - Cox, Alexander; Klümper, Niklas; Stein, Johannes; Sikic, Danijel; Breyer, Johannes; Bolenz, Christian; Roghmann, Florian Bernhard Gerhard; Erben, Philipp; Wirtz, Ralph M.; Wullich, Bernd; Ritter, Manuel; Hölzel, Michael; et al. (European urology, 2024)
Urothelial cancer (UC) care is moving toward precision oncology. For tumor biology-driven treatment of metastatic UC (mUC), molecular subtypes play a crucial role. However, it is not known whether subtypes change during metastatic evolution. To address this, we analyzed a UC progression cohort (N = 154 patients) with 138 matched primary tumors (PRIM) and synchronous or metachronous distant metastasis (MET) by immunohistochemistry, and mRNA sequencing in a subgroup of 20 matched pairs. Protein-based tumor cell subtypes and histomorphology remained stable during metastatic progression (concordance: 94%, 95% confidence interval [CI] 88-97%). In comparison, transcriptome-based molecular consensus subtypes exhibited higher heterogeneity between PRIM and MET (concordance: 45%, 95% CI 23-69%), with switches particularly occurring between luminal and stroma-rich tumors. Of note, all tumors classified as stroma rich showed luminal tumor cell differentiation. By an in-depth analysis, we found a negative correlation of luminal gene and protein expression with increasing desmoplastic stroma content, suggesting that luminal tumor cell differentiation of “stroma-rich tumors” is superimposed by gene expression signals stemming from the stromal compartment. Immunohistochemistry allows tumor cell subtyping into luminal, basal, or neuroendocrine classes that remain stable during metastatic progression. These findings expand our biological understanding of UC MET and have implications for future subtype-stratified clinical trials in patients with mUC. - Patient summary - Urothelial carcinomas (UCs) occur in different appearances, the so-called molecular subtypes. These molecular subtypes will gain importance for the therapy of metastatic UCs in the future. We could demonstrate that the subtype remains stable during metastasis, which is highly relevant for future studies.
Online verfügbar: 6. April 2023, Artikelversion: 12. März 2024
Gesehen am 16.09.2024